East Otago Taiāpure: sharing the underlying philosophies 26 years on - Anne‐Marie Jackson; Christopher D. Hepburn; Brendan Flack (New Zealand Journal of Marine and Freshwater Research, 2018)
Taiāpure (local fishery) are Customary fisheries Protection Areas (CPAs) designed to make better provision for rangatiratanga (Māori chieftainship) under Article II of te Tiriti o Waitangi. The East Otago Taiāpure was applied for in 1992 and finally gazetted in 1999. It has been twenty‐six years since the East Otago Taiāpure was applied for and the East Otago Taiāpure Management Committee has incorporated mātauranga‐ā‐hapū (sub‐tribal knowledge) as well as local knowledge to inform decision making to advocate for better management of local fisheries and ecosystems for the benefit of all people and the generations to come. We provide a narrative from over a quarter of a century of management of the East Otago Taiāpure to provide a useful reference for communities wishing to explore the taiāpure concept to realise rangatiratanga for their uri (descendants) to come.